(untitled) (Research, Society and Development, 2024)
Dental anomalies of number, such as mesiodens, are increasingly detected, and represent a subcategory of supernumerary anomalies, which is predominant in men in the permanent dentition. Its etiology is still unknown, however, there is a variety of complications that affect the dental structures of the common dentition. The most effective and optimal way to diagnose it is through images, cone beam computed tomography (CBCT) is the most appropriate to know location and shape; Therefore, it is the tool that today complements its surgical planning, ensuring a favorable prognosis. The objective of this study is to collect important and updated information about the main generalities and aspects of the mesiodens through a bibliographic review. For the development of this study, literature from different scientific sources related to mesiodens was reviewed. Of a total of 1533 scientific articles, only 36 were selected thanks to the established inclusion criteria. In conclusion, the theory most accepted by multiple studies about the origin of the mesiodens is that of hyperactivity of the dental lamina, among other genetic factors. Its diagnosis can be made through a clinical examination, however, a CBCT can allow a more explicit detection and thus visualize possible complications in the future. In addition, it is a good tool when performing surgical management, which is the only way to treat these anomalies without affecting the original permanent dentition.